Kölliker’s organ-supporting cells and cochlear auditory development - Chen, Jianyong; Gao, Dekun; Sun, Lianhua; Yang, Jun (Frontiers in Molecular Neuroscience, 2022)
The Kölliker’s organ is a transient cellular cluster structure in the development of the mammalian cochlea. It gradually degenerates from embryonic columnar cells to cuboidal cells in the internal sulcus at postnatal day 12 (P12)–P14, with the cochlea maturing when the degeneration of supporting cells in the Kölliker’s organ is complete, which is distinct from humans because it disappears at birth already. The supporting cells in the Kölliker’s organ play a key role during this critical period of auditory development. Spontaneous release of ATP induces an increase in intracellular Ca2+ levels in inner hair cells in a paracrine form via intercellular gap junction protein hemichannels. The Ca2+ further induces the release of the neurotransmitter glutamate from the synaptic vesicles of the inner hair cells, which subsequently excite afferent nerve fibers. In this way, the supporting cells in the Kölliker’s organ transmit temporal and spatial information relevant to cochlear development to the hair cells, promoting fine-tuned connections at the synapses in the auditory pathway, thus facilitating cochlear maturation and auditory acquisition. The Kölliker’s organ plays a crucial role in such a scenario. In this article, we review the morphological changes, biological functions, degeneration, possible trans-differentiation of cochlear hair cells, and potential molecular mechanisms of supporting cells in the Kölliker’s organ during the auditory development in mammals, as well as future research perspectives.